Neuropeptide Y nerve paracrine regulation of prostate cancer oncogenesis and therapy resistance. Issue 1 (6th October 2020) - Ding, Yi; Lee, MinJae; Gao, Yan; Bu, Ping; Coarfa, Christian; Miles, Brian; Sreekumar, Arun; Creighton, Chad J.; Ayala, Gustavo
Abstract: Background: Nerves are key factors in prostate cancer (PCa) progression. Here, we propose that neuropeptide Y (NPY) nerves are key regulators of cancer–nerve interaction. Methods: We used in vitro models for NPY inhibition studies and subsequent metabolomics, apoptotic and migration assays, and nuclear transcription factor‐κB (NF‐κB) translocation studies. Human naïve and radiated PCa tissues were used for NPY nerve density biomarker studies. Tissues derived from a Botox denervation clinical trial were used to corroborate metabolomic changes in humans. Results: Cancer cells increase NPY positive nerves in vitro and in preneoplastic human tissues. NPY‐specific inhibition resulted in increased cancer apoptosis, decreased motility, and energetic metabolic pathway changes. A comparison of metabolomic response in NPY‐inhibited cells with the transcriptome response in human PCa patients treated with Botox showed shared 13 pathways, including the tricarboxylic acid cycle. We identified that NF‐κB is a potential NPY downstream mediator. Using in vitro models and tissues derived from a previous human chemical denervation study, we show that Botox specifically, but not exclusively, inhibits NPY in cancer. Quantification of NPY nerves is independently predictive of PCa‐specific death. Finally, NPY nerves might be involved in radiation therapy (RT) resistance, as radiation‐induced apoptosis is reduced when PCa cells are cocultured with dorsal root ganglia/nerves and NPY positive nerves are increased in prostates of patients that failed RT. Conclusion: These data suggest that targeting the NPY neural microenvironment may represent a therapeutic approach for the treatment of PCa and resistance through the regulation of multiple oncogenic mechanisms.